2018
DOI: 10.1097/ij9.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

The top 100 most-cited articles on osteosarcoma: a bibliometric analysis

Abstract: Background: Osteosarcoma or “osteogenic sarcoma” is the most common neoplasm of the bone in children and young adults. This research is premised upon a citation analysis of the top 100 most-cited articles on osteosarcoma. Materials and Methods: This research is dependent upon the use of SCOPUS database. Using the search strategy “osteosarcoma” on this database yielded 12,107 articles. After filtering for relevant articles, the top 100 most-cited article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Bibliometric studies have been conducted on the most influential scientific articles in the fields of medicine and dentistry . However, no study has been performed on the top 100 most‐cited (“classic”) articles published in a dental journal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric studies have been conducted on the most influential scientific articles in the fields of medicine and dentistry . However, no study has been performed on the top 100 most‐cited (“classic”) articles published in a dental journal.…”
Section: Introductionmentioning
confidence: 99%
“…9 Bibliometric studies have been conducted on the most influential scientific articles in the fields of medicine and dentistry. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] However, no study has been performed on the top 100 most-cited ("classic") articles published in a dental journal. This study aims to identify and analyze the 100 most-cited articles in Periodontology 2000 since its inception, in order to delineate changing trends, dominant topics of interest, centers of excellence, and substantial advancements made over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis gives a large amount of information, such as the trends in frequently studied topics, 48,49 trends in study design, 48,50 type of articles and authorship trends, 47,51 evolution of research activity, 52 geographic origin of research articles, 48 or information specifically oriented to certain diseases or conditions. 53,54 The present study demonstrated that the vast majority of publications were in vitro and animal research (preclinical research), while a relatively lower percentage of publications were clinical. Preclinical research is performed to evaluate biologic mechanisms, treatment strategies, safety, and possible adverse event reactions to candidate materials/technologies/ devices prior to clinical research.…”
Section: Discussionmentioning
confidence: 53%
“…Since its publication in 2009, this book has been among the top 25% most downloaded e‐books in the relevant Springer e‐book collection. In particular, its chapter on the epidemiology of osteosarcoma 2 has been cited 1642 times on Google Scholar, and it is recognized as the fourth most cited article on osteosarcoma of all time on Scopus 11 …”
Section: Figurementioning
confidence: 99%